2004
DOI: 10.1055/s-2004-830371
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Acyl-CoA Dehydrogenase Deficiency Associated with Early Onset Severe Axonal Neuropathy

Abstract: Two unusual cases of axonal neuropathy associated with short-chain acyl-CoA dehydrogenase (SCAD) deficiency are described. These two unrelated infants presented with profound generalised weakness, particularly affecting the upper limbs. Clinical examination revealed generalised peripheral hypotonia and weakness, with absent deep tendon reflexes. An axonal polyneuropathy was confirmed on electromyogram (EMG) and nerve conduction studies (NCS) and, following an extensive metabolic screen, an acylcarnitine and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…From a study of 31 Dutch patients with SCADD, van Maldegem and coworkers (2006) noted that SCADD was not clinically severe and that it was not possible to differentiate diseased from nondiseased individuals (van Maldegem et al, 2006). Atypical presentation has, however, been reported, including two infants with SCADD, one who displayed early-onset severe axonal neuropathy and another who presented with brain malformation and infantile spasms (Kurian et al, 2004;Mikati et al, 2007). SCADD is relatively rare compared with MCAD and VLCAD deficiencies (Liebig et al, 2006); however, SCAD gene replacement does act as a surrogate model for MCAD and VLCAD deficiencies, which are clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…From a study of 31 Dutch patients with SCADD, van Maldegem and coworkers (2006) noted that SCADD was not clinically severe and that it was not possible to differentiate diseased from nondiseased individuals (van Maldegem et al, 2006). Atypical presentation has, however, been reported, including two infants with SCADD, one who displayed early-onset severe axonal neuropathy and another who presented with brain malformation and infantile spasms (Kurian et al, 2004;Mikati et al, 2007). SCADD is relatively rare compared with MCAD and VLCAD deficiencies (Liebig et al, 2006); however, SCAD gene replacement does act as a surrogate model for MCAD and VLCAD deficiencies, which are clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as much as 14% of the normal population is homozygous for one or compound heterozygous for both of the common ACADS gene variations. Seventy-Wve patients have so far been reported in the literature with evidence of impaired SCAD enzyme function, that is, elevated EMA in urine, increased butyrylcarnitine accumulation in blood or cultured Wbroblasts, and/or reduced SCAD enzyme activity in Wbroblast cultures or muscle tissue (Amendt et al 1987;Baerlocher et al 1997;Bhala et al 1995;Birkebaek et al 2002;Bok et al 2003;Coates et al 1988;Corydon et al 2001;Dawson et al 1995;Koeberl et al 2003;Kurian et al 2004;Matern et al 2001;Mikati et al 2007;Ribes et al 1998;Seidel et al 2003;Sewell et al 1993;Tein et al 1999;Turpin and Tobias 2005;van Maldegem et al 2006;Young et al 2003). Molecular genetic analysis demonstrated that most of these individuals (60 of 67 investigated) have a genotype deWned by the common variations alone or by one of the common variations in combination with a rare variation (Amendt et al 1987;Birkebaek et al 2002;Bok et al 2003;Corydon et al 2001;Gregersen et al 1998;Koeberl et al 2003;Kurian et al 2004;Matern et al 2001;Naito et al 1990;Seidel et al 2003;Tein et al 2007;van Maldegem et al 2006;Young et al 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Till date, 25 patients have been identified and 50 reported worldwide based upon reduced or absent SCAD activity in vitro [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Genotype-phenotype correlations have been inconsistent [8,18].…”
Section: Discussionmentioning
confidence: 99%